Analysis of phenylbutazone residues in horse tissues with and without enzyme‐hydrolysis by LC‐MS/MS. Issue 5 (May 2016) - Boison, Joe O.; Dowling, Trisha; Johnson, Ron; Kinar, Jana
Abstract : Phenylbutazone (PBZ) is permitted to be used for the treatment of musculoskeletal pain and inflammation in race horses but it is not approved for use in horses destined for human consumption. In a recent study initiated in our laboratory to study the disposition of PBZ and its oxyphenbutazone (OXPBZ) metabolite in equine tissues, we compared the effect of an additional enzymatic hydrolysis step with ß‐glucuronidase on the results of the analysis for PBZ without enzymatic hydrolysis. Incurred tissue samples obtained from a female horse dosed with PBZ at 8.8 mg/kg for 3 days and sacrificed 6 days following the last administration were used for this study. Liver, kidney, and muscle tissues were collected, extracted, cleaned up on a silica‐based solid‐phase extraction (SPE) preceded by a weak‐anion exchange SPE and analyzed with our in‐house validated liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) method for PBZ and OXPBZ. Addition of the hydrolysis step resulted in a significant increase in recovery of both PBZ and OXPBZ residues. © 2016 Her Majesty the Queen in Right of Canada. Drug Testing and Analysis © 2016 John Wiley & Sons, Ltd. Abstract : Without hydrolysis, the concentration of PBZ in equine tissue harvested six days post mortem was in the order liver > kidney >> muscle. The concentration of OXPBZ was highest in kidney followed by liver and was below the LOQ for muscle. With hydrolysis PBZ and OXPBZ concentrations were elevated in all tissues to permit the detection of quantifiable concentrations in even muscle tissues.